ANALISIS PENGENDALIAN KUALITAS PRODUK DENGAN MENGGUNAKAN STATISTICAL QUALITY CONTROL (SQC) PADA USAHA AMPLANG KARYA BAHARI DI SAMARINDA - Maulida Silvia Arianti; Emy Rahmawati; Raden Roro Yulianti Prihatiningrum (Universitas Lambung Mangkurat, 2020)
The objectives of this study are: (i) To analyze the quality control of the products applied to the Amplang Karya Bahari business based on Statistical Quality Control (SQC) tools, (ii) To find out and analyze what factors cause product damage / disability at the Amplang Karya Bahari business in Samarinda.This research method uses quantitative quantitative discretionary research method that is research that is used to investigate, find, describe, and explain the quality or features of social influences that cannot be explained, measured or described through a quantitative approach. The operational definitions of this research are (i) Quality control processes, (ii) Quality control measures. Types and sources of data use primary data obtained directly from the object of research. Data collection techniques are (i) observation, (ii) interviews, (iii) documentation, (iv) laboratory tests. Analysis of the data used are: (i) collecting data (check sheet), (ii) histogram,(iii) making control charts, (iv) causal diagrams, (v) proposed improvements.Keywords: Quality Control, and Maintaining Quality.